THE INFLUENCE OF EARNINGS MANAGEMENT ON FIRM PERFORMANCE: DOES GENDER DIVERSITY MATTER? - Rahmawati, Fani Putri; Widiyati, Dian; Isnatsaqif, Hanif (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
The goal of this study is to ascertain how earnings management influences firm performance and whether board gender diversity can either enhance or weaken this relationship. The sample comprises 21 property and real estate firms that were listed on the Indonesia Stock Exchange (IDX) between 2019 and 2023, which is analyzed using moderation regression analysis and the panel data approach. Results indicate that earnings management has a significant positive effect on firm performance, as reflected in the Return on Assets (ROA), supporting the view that it is used to meet short-term targets. However, gender diversity does not significantly moderate this relationship. These findings suggest that gender diversity has not effectively enhanced management, indicating the need for further evaluation of board composition to strengthen oversight.